La déprédation marine depuis le Parc naturel marin d’Iroise (Bretagne) : enseignements du volet d’enquêtes ethnographiques du programme scientifique pluridisciplinaire INPECMAM-Iroise (INteractions PÊChe MAMmifères marins) - Émilie Mariat-Roy; Claire Laspougeas (VertigO)
This article offers a retrospective look at the ethnographic survey component of the INPECMAM-Iroise multidisciplinary scientific program (INteractions PÊChe MAMmifères marins) in the Iroise Marine Natural Park in light of the "oceanic turning point" that has been affecting research in the human and social sciences over the last decade. A better understanding of the state of the marine environment and human-nature relationships is a common objective for managers and users of professional fishing. In this context, the study of marine depredation has emerged as an object with high heuristic value. Indeed, the latter does not impose itself on anyone as obvious or immediately as entirely stabilized in what is par excellence an environment of predation and hazards. The study of depredation, the qualifications and characterization of the latter by professional fishermen, are revealing of the environmental knowledge and of empirics and episteme that the very methodology of the IMPECMAM program has made it possible to apprehend in an original and pioneering way. The latter cannot be considered independently of the governance frameworks of an area whose main vocation of improving knowledge and promoting the balance between the protection of the marine environment and the sustainable development of maritime activities, is likely to be disputed at any time.